Spatial history and genetic-morphological variation of populations of Belostoma angustum Lauck, 1964 (Heteroptera: Belostomatidae) throughout Pampas highlands in Rio Grande do Sul, Brazil - Stefanello, Fabiano (2017)
We investigated the population dynamics of the giant water bug, Belostoma angustum, across highland sin the Pampas of southern Brazil. We evaluated genetic and morphological variation, as well as the demographic history of 18 populations. The overall range includes two highlands and a lowland between them, overall exceeding 400 kilometers along the longitudinal gradient. Genetic variation was assessed from mitochondrial and nuclear markers. The morphological variation was estimated using linear measurements of males and females, and from male genitalic structures using geometric morphometrics approaches. We evaluated the effect of the highland topography, drainage basins, and past climate changes on the population structure. Our results from multiple analyses of molecular variance (AMOVA) show that Belostoma angustum structures as a large panmictic population across the Pampas highlands range. Every most frequent haplotype is shared by individuals from all three sampled areas in genetic markers from the mitochondrial as well as from the nuclear locus. Differentiation among haplotypes was very low, not greater than two mutation steps. The congruent phylogeographical pattern in both markers indicate absent sex-biased migration rates. Furthermore, there was no evidence for isolation-by-distance (IBD) based on the mitochondrial data. The pairwise st was low and not significant, indicating historical gene flow among populations of the giant water bug studied throughout Pampas highlands. Our findings about the demographic history of panmictic population throughout Pampas highlands suggest it experienced recent and rapid population expansion that started in the Late Pleistocene period, approximately 15,000 years old after Last Glacial Maximum. The recent marked demographic expansion could explain the high percentage of the exclusive haplotypes and the very low mutational steps among them. We did not find morphological variation among populations of B. angustum throughout Pampas highlands reflected, except for some body dimensions. The overall phenotypic uniformity among populations becomes more likely if gene flow is hypothesized to homogenize populations. However, in the body size, specially, there was variation among populations potentially explained by phenotypic plasticity, thereby generating phenotypic diversity without genetic differentiation. Our genetic findings suggest indirectly that individuals of B. angustum are strong fliers able to overcome the topographical barriers of the sampled area.